High-Affinity Methane Oxidation by a Soil Enrichment Culture Containing a Type II Methanotroph - Dunfield, Peter F. (American Society for Microbiology, 1999)
Methanotrophic bacteria in an organic soil were enriched on gaseous mixing ratios of <275 parts per million of volume (ppmv) of methane (CH(4)). After 4 years of growth and periodic dilution (>10(20) times the initial soil inoculum), a mixed culture was obtained which displayed an apparent half-saturation constant [K(m(app))] for CH(4) of 56 to 186 nM (40 to 132 ppmv). This value was the same as that measured in the soil itself and about 1 order of magnitude lower than reported values for pure cultures of methane oxidizers. However, the K(m(app)) increased when the culture was transferred to higher mixing ratios of CH(4) (1,000 ppmv, or 1%). Denaturing gradient gel electrophoresis of the enrichment grown on <275 ppmv of CH(4) revealed a single gene product of pmoA, which codes for a subunit of particulate methane monooxygenase. This suggested that only one methanotroph species was present. This organism was isolated from a sample of the enrichment culture grown on 1% CH(4) and phylogenetically positioned based on its 16S rRNA, pmoA, and mxaF gene sequences as a type II strain of the Methylocystis/Methylosinus group. A coculture of this strain with a Variovorax sp., when grown on <275 ppmv of CH(4), had a K(m(app)) (129 to 188 nM) similar to that of the initial enrichment culture. The data suggest that the affinity of methanotrophic bacteria for CH(4) varies with growth conditions and that the oxidation of atmospheric CH(4) observed in this soil is carried out by type II methanotrophic bacteria which are similar to characterized species.